Electromechanical motion devices : rotating magnetic field-based analysis with online animations.: rotating magnetic field-based analysis with online animations. (2020) - Krause, Paul C; Wasynczuk, Oleg; Pekarek, Steven; O'Connell, Timothy
No abstract available